Ideological aspects in the dubbing of Física o Química - Romero, Lupe; De Laurentiis, Antonella (MonTi Monografías de Traducción e Interpretación, 2018)
The general aim of this paper is to present the initial results of a descriptive study of the Italian dubbing of the Spanish television series Física o Química [Physics or Chemistry]. Física o Química is set in a secondary school in Madrid. Its main characters are teenagers and teachers, and its storyline revolves around the relationships between them. The series features dialogues containing many colloquial and rude expressions typical of the language used by youngsters, as well as scenes portraying youngsters’ interest in religion, sex, drugs, and social groups. The paper shows the impact of ideological orientations on the translated version, and how this has led to distortions, altered meanings or even the complete removal of elements deemed taboo.